O uso da gamificação no ensino de física - SENA, Edson Ferreira de (2024)
Bearing in mind that in these pandemic times, education professionals sought more didactic ways to develop their classes, in order to improve the absorption of content by students, research on the use of gamification in the teaching of physics, in order to present the gamification as an alternative capable of generating student engagement, motivating, modifying behaviors in order to improve the teaching of physics. Therefore, it is necessary to present what gamification is, to present the elements of games, to describe the processes, and to present the application of gamified activities related to the teaching of physics developed in the classroom, and the results achieved. A research is then carried out at the State School of Elementary and High School Professor Temístocles de Araújo during the second semester of 2019, that is, before the pandemic, and at the UFPa facilities in the second semester of 2020, during the classes taught in the discipline Physical Statistic I. Therefore, there is the application of gamified activities in the Temístocles de Araujo school where students participated in groups formed by 5 students, there was a greater engagement between them and a change in behaviors, which did not happen in conventional classes. Regarding the application of gamification in the classes of statistical physical discipline taught at a distance by UFPa, it was evident that even though the classes were not in person, the use of gamification allowed them to become pleasant and with a good interaction between teacher and student. What imposes the observation that gamification is an active methodology that can be used both in classroom and in non-classroom teaching, bringing good results.